Syntheses, crystal structures and photophysical properties of Cu(ii) complexes: fine tuning of a coordination sphere for selective binding of azamethiphos. Issue 3 (23rd December 2016) - Raj, Pushap; Singh, Amanpreet; Singh, Ajnesh; Singh, Narinder
Abstract : We have synthesized two copper complexesC1–2 and these complexes were explored as chemosensors for selective binding with azamethiphos. Abstract : Two copper complexesC1 andC2 have been designed and developed for selective sensing of organophosphates. It is important to develop an efficient method for the detection of these agents for environmental analysis because the overuse of these agents in the environment causes harmful effects on living systems. Our attempts to utilize the copper complexes for the detection of organophosphates remained successful: theC1 complex has shown selective binding for the azamethiphos with a detection limit of 19 nM; while theC2 complex has not revealed any selectivity for any of the tested organophosphates. The results indicated that the coordination sphere of theC1 complex is proficiently engineered in such a way that it offers judicial binding sites for guest molecules.